Reliability test for subsea power semiconductors. (November 2020) - Guillon, David; Scherrer, Barbara; Dugal, Franc; Lendenmann, Heinz; Oppliger, Jean-Marc
Abstract: Following the demand from a new domain of application, a test setup was developed to evaluate the performance of high-power semiconductor device when exposed to a dielectric liquid and high pressure. The specific test conditions were established to emulate the conditions inside a tank place in a deep-sea environment. Those conditions can be characterized by two key parameters: the pressure and the chosen dielectric/thermal liquid. The power semiconductor device is to be tested at high and low temperature to simulate operation under maximum load as well as when turned off, respectively. The reliability tests outlined here serve to support the development and the validation of Subsea technology for semiconductors power modules.